Republic of Slovenia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This paper focuses on the following key issues of the Slovenian economy: export competitiveness, corporate financial health and investment, European Central Bank (ECB) quantitative easing, and financial sector development issues and prospects. Slovenia's exports have been the main contributor to GDP growth in recent years. In particular, by 2015 exports of goods and services had increased by 20 percentage points of GDP compared to their postcrisis low in 2009. Preceding the global economic slump in 2008, bank credit in Slovenia fueled corporate investment. The past few years have witnessed substantial monetary easing by the ECB. With inflation running well below target, the ECB has been pursuing unconventional monetary policy-easing actions.